Case report of familial COVID-19 cluster associated with High prevalence of anosmia, ageusia, and gastrointestinal symptoms - Ho, Bethany E.; Ho, Andrea P.; Ho, Michaela A.; Ho, Elizabeth C. (IDCases, 2020)
•COVID-19 may present with sensory symptoms like anosmia and ageusia.•Similarly to other coronaviruses, SARS-CoV-2 may cause GI disturbances.•GI symptoms may be attributable to SARS-CoV-2 replication in GI epithelia.•COVID-19 can present with wide variation in symptoms and duration observed. Patients with COVID-19 most commonly report respiratory symptoms, with a minority reporting gastrointestinal (GI) symptoms in currently available reports. Additionally, little is known about the symptoms of anosmia/hyposmia, ageusia, and dysgeusia anecdotally seen in COVID-19 patients, which may potentially be considered both GI and sensory/neurological manifestations of infection. We hope to clarify the prevalence of these symptoms and patterns of transmission within a family cluster. We interviewed 7 patients via oral inquiries and a questionnaire, collecting data on subject symptoms and their durations. Reverse transcriptase-polymerase chain reaction (RT-PCR) was used to confirm 2 of these cases. We report a familial cluster of 5 presumed and 2 confirmed COVID-19 cases, all of whom reported one or more GI symptoms and 5 of whom reported sensory symptoms of anosmia/hyposmia, ageusia/hypogeusia, and/or dysgeusia. This frequency of GI symptoms is high relative to currently available epidemiological reports, which also infrequently report on sensory symptoms. COVID-19 exhibits wide variation in duration, severity, and progression of symptoms, even within a familial cluster.